2015
DOI: 10.1126/scitranslmed.3010329
|View full text |Cite
|
Sign up to set email alerts
|

NPC1L1 is a key regulator of intestinal vitamin K absorption and a modulator of warfarin therapy

Abstract: Vitamin K (VK) is a micronutrient that facilitates blood coagulation. VK antagonists, such as warfarin, are used in the clinic to prevent thromboembolism. Because VK is not synthesized in the body, its intestinal absorption is crucial for maintaining whole-body VK levels. However, the molecular mechanism of this absorption is unclear. We demonstrate that Niemann-Pick C1-like 1 (NPC1L1) protein, a cholesterol transporter, plays a central role in intestinal VK uptake and modulates the anticoagulant effect of war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 28 publications
1
77
0
Order By: Relevance
“…The Abcg2 KO mice (Ichida et al, 2012) had been maintained in our laboratory as described previously. All the animals were housed in temperature- and humidity-controlled animal cages with a 12-h dark-light cycle, and free access to water and standard animal chow (MF, Oriental Yeast Company, Tokyo, Japan) as described previously (Ito et al, 2014; Takada et al, 2015). In the present study, all the in vivo experiments were conducted with 6–8-week-old male mice.…”
Section: Methodsmentioning
confidence: 99%
“…The Abcg2 KO mice (Ichida et al, 2012) had been maintained in our laboratory as described previously. All the animals were housed in temperature- and humidity-controlled animal cages with a 12-h dark-light cycle, and free access to water and standard animal chow (MF, Oriental Yeast Company, Tokyo, Japan) as described previously (Ito et al, 2014; Takada et al, 2015). In the present study, all the in vivo experiments were conducted with 6–8-week-old male mice.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we also revealed that ezetimibe can inhibit the intestinal absorption of these fat-soluble vitamins in mice and rats. 56,58) Our findings suggest that intestinal absorption of vitamin E and vitamin K 1 is mediated by ezetimibe-sensitive NPC1L1-dependent pathway (Fig. 2).…”
Section: Physiological Substrates Of Npc1l1 Other Than Sterols and Pomentioning
confidence: 91%
“…Interestingly, it has been reported that anticoagulant activity of warfarin is enhanced by combination with ezetimibe. 58,63,64) Figure 4A shows typical cases of the ezetimibe-warfarin interaction found by our retrospective survey of clinical records at the University of Tokyo Hospital. 58) Although the mechanism of this drug-drug interaction was not clear, we recently demonstrated that ezetimibe-related vitamin K 1 malabsorption causes reduction in hepatic vitamin K 1 amounts, resulting in an unintentional enhancement of anticoagulant activity in almost all (more than 85%) patients taking both warfarin and ezetimibe simultaneously 58) (Fig.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations